Goalkeeper's position for defending short range shots - Jonghyun, Y.; Youngsoo, P.; Kitae, K.; Je-Kwang, R. (International Journal of Sports Science & Coaching, 2017)
The purpose of the study was to analyze and quantify the ability of the goalkeeper while defending shots from left and right sides of penalty area or the goal area, which frequently occurs in an actual game situation. In other words, the study aimed at verifying the reaction ability of the goalkeeper to defend goals in two different defense positions across a 3m width area without performing dives. Eleven male goalkeepers from a university soccer league participated in the study. The goalkeepers were assigned to react to a specific target point, i.e. high, middle, low, left and right in response to the LED signal positioned at the front. Three-dimensional motion analysis system was used to perform kinematical analysis through which variables such as the approach time of reaching specific target points and the movement used to cover the defensive area were observed. In results, no significant differences were observed in approach time of the hand to the target point in both defense positions, i.e. Type-A (defense posture of positioning the hand at knee height) and Type-B (defense posture of positioning the hand at waist height). But Type-B defense position average velocity was observed faster than Type-A for blocking shots of low-middle heights. Hence, the results obtained from the study showed a possibility that being prepared in Type-A defense position will be more accurate and stable. Moreover, goalkeepers were able to occupy wider defense range in Type-A defense position than Type-B within the time period of 0.7~0.8 s after triggering of the LED signal. In conclusion, the results obtained from the study pointed out that Type-A defense position can be much more effective in soccer for blocking shots from the left and right sides of the penalty area. The defense posture of positioning the hand at low height is considered more effective when defending a ball shot from areas near the penalty area than the high hand position. It was also confirmed that the available defense area can be defended widely and effectively by moving the center of the body. Further studies need to be performed to consider the cognitive perspective by applying various methods. ABSTRACT FROM AUTHOR